ANALISIS KOMPARASI PERSEPSI STAKEHOLDERS MENGENAI TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN SEKOLAH : Studi Komparatif pada Sekolah Menengah Atas Negeri dan Swasta di Kabupaten Karawang - Karlina, Gina (2016)
This research aims to analyze the differences in perception between stakeholders in public senior high school and stakeholders in private senior high school on the transparency of school's financial management and to analyze the differences in perceptions between stakeholders in public Senior high school and stakeholders in private Senior high school on the accountability of school's financial management. The population used was public senior high school and private Senior high school in the Karawang regency many as 37 schools. The sampling technique used was purposive sampling. While the sample used is amounted to 20 schools, including 10 public Senior high school and 10 private senior high school. The method used is comparative descriptive method with quantitative approach. Hypothesis test used is 2 difference test technique which is t-test independent two sample and Mann Whitney test after the normality test is done The results showed differences in the perception of stakeholders in public senior high school and private senior high school towards transparency of school's financial management on high schools in Karawang, existence of different perceptions of stakeholders in public senior high school and private senior high school towards accountability in schools financial management on high schools in Karawang Keywords: Stakeholder Perception, Transparency, Accountability, Schools Financial Management Penelitian ini bertujuan untuk menganalisis perbedaan persepsi antara stakeholder di SMA Negeri dan stakeholder di SMA Swasta terhadap transparansi pengelolaan keuangan sekolah dan untuk menganalisis perbedaan persepsi antara stakeholder di SMA Negeri dan stakeholder di SMA Swasta terhadap akuntabilitas pengelolaan keuangan sekolah. Populasi yang digunakan adalah SMA Negeri dan SMA Swasta se-Kabupaten Karawang sebanyak 37 sekolah. Adapun teknik sampel yang digunakan adalah purposive sampling. Sedangkan sampel yang digunakan sebanyak 20 sekolah, diantaranya 10 SMA Negeri dan 10 SMA Swasta. Metode penelitian yang digunakan adalah metode deskriptif komparatif dengan pendekatan kuantitatif. Uji hipotesis yang digunakan adalah 2 teknik uji beda yaitu t-test independent two sample dan uji Mann Whitney setelah sebelumnya dilakukan uji beda normalitas. Hasil penelitian menunjukan adanya perbedaan persepsi stakeholder di SMA Negeri dan SMA Swasta terhadap transparansi pengelolaan keuangan sekolah di SMA se-Kabupaten Karawang, Adanya perbedaan persepsi stakeholder di SMA Negeri dan SMA Swasta terhadap akuntabilitas pengelolaan keuangan sekolah di SMA se-Kabupaten Karawang Kata Kunci : Persepsi Stakeholder, Transparansi, Akuntabilitas, Pengelolaan Keuangan Sekolah